Utilization of Digital Media Based on Local Wisdom in Learning Folk Poetry: A Qualitative Study on Junior High School Students - Senniaty Sarira, Faskalia; Baan, Anastasia; Gasong, Dina (Universitas Muhammadiyah Makassar, 2024)
Learning folk poetry in Indonesian subjects has its own challenges, especially in instilling a deep understanding to students. This study aims to explore the utilization of local wisdom-based digital media in improving students' understanding of folk poetry. Using a qualitative research approach with a case study method, this research was conducted at SMP Negeri 4 Sesean Satap involving teachers and students as the main participants. Data were collected through observation, in-depth interviews, and analysis of learning documents. The results show that the use of digital media that integrates local cultural elements, such as audio-visual folk poetry and interactive applications, can increase students' engagement and understanding in learning. Students find it easier to interpret the meaning of folk poetry when the material is presented through more contextual and interesting media. In addition, teachers also benefit in delivering the material more effectively. The conclusion of this study confirms that the utilization of digital media based on local wisdom can be an innovative solution in learning folk poetry. The implication of this research leads to the development of learning media that is more adaptive and in accordance with the needs of students in areas with high cultural wealth.